The Peran Agama terhadap Problematika Remaja (Dalam konteks pemikiran Ibn Rushd 1126-1198 M) - Imroatus Sholikha Azzuhriyyah; Achmad Khudori Soleh (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2023)
Ibn Rushd said that the real main goal of Islamic law is correct knowledge and right actions (al-ilmulhaq wal-amalul-haq). Because the teachings contained in the Islamic religion have laws and rules that are binding. The purpose of writing this article is to analyze the role of religion in adolescent problems in terms of Ibn Rushd's thoughts. The method used in this study is a qualitative research method with a library research approach. The results of this study state that (1) Adolescent problems include adjustment: depression, bullying, gadget addiction. Diversity: polytheists, leaving the Shari'a just like that, degradation of morality. Health: drugs, alcohol, smoking. Economy: stealing, kidnapping, robbery and others. (2) Religion (in the context of Ibn Rushd's thought) has 3 main sources, namely revelation, reason, and revelation + reason which both have their own function in determining adolescent behavior. (3) Knowledge of religion is needed in directing youth so that youth can determine attitudes, behavior, and get along with others, and religion also has a function as a social controller, meaning that individuals believe that religious teachings are the norm in social life and can prevent individuals from committing things that are prohibited by religion or violate applicable regulations.